2018
DOI: 10.21037/jtd.2018.05.43
|View full text |Cite
|
Sign up to set email alerts
|

Single-port video-assisted thoracic surgery (VATS)—advanced procedures & update

Abstract: The uniportal approach for major pulmonary resections began in 2010, with the first case being reported by D González-Rivas and colleagues in La Coruña, Spain. Since then, in different countries, thoracic surgeons had been performing hundreds of cases, with more advanced and complex procedures. Nowadays, there are reports of uniportal tracheal resection and reconstruction, carinal resection, bronchoplastic procedures, lobectomies with chest wall excision, and vascular reconstruction with optimal outcomes. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 54 publications
(74 reference statements)
0
19
0
Order By: Relevance
“…Uniportal VATS was pioneered by Rocco for wedge pulmonary resections in 2004 and was gradually extended by Dr. Diego Gonzalez-Rivas for other thoracic operations (12,13). Compared with conventional multiportal VATS, uniportal VATS has unique characteristics in terms of further improvements in cosmesis, an optimized visual field, reduced postoperative pain and a better quality of life for patients.…”
Section: Discussionmentioning
confidence: 99%
“…Uniportal VATS was pioneered by Rocco for wedge pulmonary resections in 2004 and was gradually extended by Dr. Diego Gonzalez-Rivas for other thoracic operations (12,13). Compared with conventional multiportal VATS, uniportal VATS has unique characteristics in terms of further improvements in cosmesis, an optimized visual field, reduced postoperative pain and a better quality of life for patients.…”
Section: Discussionmentioning
confidence: 99%
“…More time and experience will be needed to answer this question, but for now the major limitation seems to be the experience of the surgical team with VATS. Reports available have shown that in the hands of highly experience VATS surgeons and anesthesiologists this approach is a feasible option for patients afflicted with this advanced stage lung cancers (4).…”
Section: Review Articlementioning
confidence: 99%
“…From the different approaches in VATS surgery, uniportal VATS has experience in the last decade a rapid and continuous development in terms of its application for more advance cases and complex procedures (3,4). The surgical procedure by itself is not different from open surgery and multiport VATS, so the oncological principles are not compromised.…”
Section: The Rise Of the Uniportal Approachmentioning
confidence: 99%
“…The removal of an entire lung lobe is called a lobectomy, and video‐assisted thoracoscopic surgery (VATS) lobectomy has become a minimally invasive surgical procedure for lung cancer resection (Guido‐Guerrero et al., 2018 ; Nachira et al., 2018 ; Buitrago and Restrepo, 2019 ; Raveglia et al., 2019 ). It becomes a routine preparatory step that an indwelling urinary catheter is used to prevent intraoperative urinary retention (Van Backer et al., 2019 ) in VATS lobectomy.…”
Section: Introductionmentioning
confidence: 99%